PENGARUH POLITIK DALAM PERKEMBANGAN PRAKTIK EKONOMI ISLAM DI INDONESIA - Nur Kholis (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2013)
The article below attempt to analize the influence of Indonesian politics to the development of islamic economics practices in Indonesia, especially situation and condition of Indonesian politics in the New Order Era and the reformation era. The article find that the influence of situation and condition of politics transformed in Indonesian political economy oriented to Islamic economic system in developing Islamic economic practice is very signifinace. Politics of the New Order Era bounded the development of Islamic economic practice. Politics of the reformation era supported the development of Islamic economic practice. It was proven by a rapid progress of Islamic economic practice in the area of Islamic banking, Islamic insurance, Islamic capital market, Sukuk, Islamic unit trust/mutual fund, Islamic microfinance institution, and Islamic public finance in the reformation era because of political condition and situation support.